Fucose Ameliorate Intestinal Inflammation Through Modulating the Crosstalk Between Bile Acids and Gut Microbiota in a Chronic Colitis Murine Model. Issue 6 (3rd February 2020) - Ke, Jun; Li, Ying; Han, Chaoqun; He, Ruohang; Lin, Rong; Qian, Wei; Hou, Xiaohua
Abstract : Fucose ameliorated colitis through restoration of crosstalk between bile acid and gut microbiota. Elevated hepatic bile acid synthesis in DSS mice was suppressed by farnesoid X receptor activation due to the reduction of its reduced antagonist, which is deconjugated by specific microbes. Abstract: Background: Recurrent intestinal inflammation is frequently associated with aberrant bile acid profiles and microbial community. Fucose exerts a protective effect on commensal bacteria in the case of intestinal pathogen infection. We speculated that fucose might also have certain impact on the microbial ecosystem under the chronic colitis setting. Methods: To validate our hypothesis, multi-omics examination was performed in combination with microbiomics and metabonomics in a chronic dextran sulfate sodium (DSS) murine model in the presence or absence of fucose. The 16S RNA sequencing was carried out to determine the ileum and colon microbiota. Primary and secondary bile acids, together with the respective taurine and glycine conjugates, were quantified through ultraperformance liquid chromatography coupled with mass spectrometry (UPLC-MS). Moreover, enzymes involved in regulating bile acid synthesis were also detected. Finally, an experiment was carried out on the antibiotic-treated mice to examine the role of gut microbiota. Results: Administration of exogenous-free fucose markedly alleviated the inflammatory response in colitis mice. In addition, excessive intestinal bile acid accumulated in DSS mice was decreased in the presence of fucose, along with the restoration of the compromised regulation on hepatic bile acid synthesis. Moreover, the shifts in bile acid profiles were linked with the improved gut microbiome dysbiosis. However, the protective effects of fucose were abolished in mice treated with antibiotic cocktail, indicating that microbiota played a pivotal role. Conclusions: Findings in this study suggest that fucose ameliorates colitis through restoring the crosstalk between bile acid and gut microbiota.